Statistical Methods for the Evaluation of University Systems - Attanasio, Massimo; Capursi, Vincenza (Contributions to Statistics, 2011)
This book presents a collection of statistical methods and procedures to assess data coming from educational systems. The topics examined include: statistical methods for constructing composite indicators, applied measurements, assessment of educational systems, measurement of the performance of the students at Italian universities, and statistical modeling for questionnaire data. Other issues are the implications of introducing different assessment criteria and procedures to the Italian university system.